Tool wear and energy consumption optimization in EDM of chromium tool steel. (2021) - Anand, B.; Giri, A.; Mohanty, C.P.; Sharma, D.
Abstract: The machining feasibility of high chromium tool steel using the EDM process has been studied. An attempt has been made to optimise the EDM process, concerning eco-friendly aspects like relative electrode wear ratio, process energy consumption along with machining parameter, that is process time. The four control factors: Peak current, Pulse duration, Flushing pressure and Dielectric level were selected to minimize the output responses. The Taguchi approach was used to optimise the process parameters. It was observed that the output responses were greatly influenced by the peak current and the dielectric level, but least affected by pulse duration.